2010
DOI: 10.1186/1741-7015-8-63
|View full text |Cite
|
Sign up to set email alerts
|

Normalisation process theory: a framework for developing, evaluating and implementing complex interventions

Abstract: BackgroundThe past decade has seen considerable interest in the development and evaluation of complex interventions to improve health. Such interventions can only have a significant impact on health and health care if they are shown to be effective when tested, are capable of being widely implemented and can be normalised into routine practice. To date, there is still a problematic gap between research and implementation. The Normalisation Process Theory (NPT) addresses the factors needed for successful implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
1,062
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,031 publications
(1,149 citation statements)
references
References 32 publications
7
1,062
0
4
Order By: Relevance
“…In addition Normalisation Process Theory (NPT) now forms a critical framework for us to understand how to implement a complex intervention such as Bridges self-management support into everyday clinical practice, so that it becomes 'normalised' Murray et al, 2010). Within the framework, implementation is defined as a complex and emergent social process, in which healthcare professionals collectively produce and embed new practices into their everyday work .…”
Section: Telling the Whole Story Beyond Efficacy Testingmentioning
confidence: 99%
“…In addition Normalisation Process Theory (NPT) now forms a critical framework for us to understand how to implement a complex intervention such as Bridges self-management support into everyday clinical practice, so that it becomes 'normalised' Murray et al, 2010). Within the framework, implementation is defined as a complex and emergent social process, in which healthcare professionals collectively produce and embed new practices into their everyday work .…”
Section: Telling the Whole Story Beyond Efficacy Testingmentioning
confidence: 99%
“…Another useful contribution of Normalisation Process Theory (previously highlighted in the Introduction section) is the explicit attention to how trial parameters can be optimised, thus assisting in the design of robust, feasible and meaningful randomised controlled trials [23]. As previously described in the Introduction, this initial study was carried out prior to three linked trials, evaluating the use of different visualisation tools with people with stroke within three different contexts.…”
Section: " the Main Features Of The Tool Are That (It) Is Proven To Bmentioning
confidence: 99%
“…Table 2 identifies and defines the four core constructs through which normalisation (or the routine embedding of a practice) occurs [22]. Murray et al (2010) [23] propose that the perspectives of health care service providers about complex health interventions and practices are an important determinant of their successful implementation within routine health care. We therefore wanted to explore the potential utility of NPT in understanding the possible challenges and facilitators to the routine use of the novel technology used within this study, as suggested in discussion about wider practices of rehabilitation professionals.…”
Section: Insert Table 1 About Herementioning
confidence: 99%
“…398 At the other end we might have a relatively finished and concrete example, such as a new prescription medicine, for which the uses and market niche are well defined and the prescriber can trial the product with relatively little disruption to everyday practice. Towards the centre of the continuum we might find instances such as telecare or educational packages that have more profound implications for changes in existing roles and workload, but which are nevertheless discrete and relatively specific.…”
Section: Understanding the Amp Modelmentioning
confidence: 99%